Considerations for Measuring Activity-Dependence of Recruitment of Synaptic Vesicles to the Readily Releasable Pool - Wesseling, John F. (Frontiers in Synaptic Neuroscience, 2019)
The connection strength of most chemical synapses changes dynamically during normal use as a function of the recent history of activity. The phenomenon is known as short-term synaptic plasticity or synaptic dynamics, and is thought to be involved in processing and filtering information as it is transmitted across the synaptic cleft. Multiple presynaptic mechanisms have been implicated, but large gaps remain in our understanding of how the mechanisms are modulated and how they interact. One important factor is the timing of recruitment of synaptic vesicles to a readily-releasable pool. A number of studies have concluded that activity and/or residual Ca2+ can accelerate the mechanism, but alternative explanations for some of the evidence have emerged. Here I review the methodology that we have developed for isolating the recruitment and the dependence on activity from other kinds of mechanisms that are activated concurrently.